Transcriptome sequencing reveals the effects of circRNA on testicular development and spermatogenesis in Qianbei Ma goats - Tang, Wen; Xu, Qiang Hou; Chen, Xiang; Guo, Wei; Ao, Zheng; Fu, Kaibin; Ji, Taotao; Zou, Yue; Chen, Jing Jia; Zhang, Yuan (Frontiers in Veterinary Science, 2023)
ircular RNAs (circRNAs) play an important role in regulating the mammalian reproductive system, especially testicular development and spermatogenesis. However, their functions in testicular development and spermatogenesis in the Qianbei Ma goat, the Guizhou endemic breed are still unclear. In this study, tissue sectioning and circRNAs transcriptome analysis were conducted to compare the changes of morphology and circular RNAs gene expression profile at four different developmental stages (0Y, 0-month-old; 6Y, 6-month-old; 12Y, 12-month-old; 18Y, 18-month-old). The results showed that the circumferences and area of the seminiferous tubule gradually increased with age, and the lumen of the seminiferous tubule in the testis differentiated significantly. 12784 circRNAs were detected from testicular tissues at four different developmental stages by RNA sequencing, and 7896 DEcircRNAs (differentially expressed circRNAs) were found in 0Y vs. 6Y, 6Y vs. 12Y, 12Y vs. 18Y and 0Y vs. 18Y. Functional enrichment analysis of the source genes showed that they were mainly enriched in testicular development and spermatogenesis. In addition, we selected 81 highly expressed DEcircRNAs from the four comparison groups, constructed a ceRNA network, and obtained some candidate circRNAs related to testicular development and spermatogenesis. Such as circRNA_07172, circRNA_04859, circRNA_07832, circRNA_00032 and circRNA_07510. These results will help to reveal the mechanism of circRNAs in testicular development and spermatogenesis, and also provide some guidance for goat reproduction.